RANCANG BANGUN GAME EDUKASI MATH FRACTION ADVENTURE BERBASIS MOBILE MATA PELAJARAN MATEMATIKA PADA MATERI PECAHAN SISWA KELAS V DI SD AL ISLAM 2 JAMSAREN - Abdullah Husin Bukhori; Anita Trisiana; Alfonsa Maria Sofia Hapsari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to design and develop a mobile-based educational game entitled "Math Fraction Adventure" as a mathematics learning medium, particularly on fraction material for fifth-grade students at SD Al Islam 2 Jamsaren, while also assessing its feasibility. This study employed a Research and Development (R&D) method using the ADDIE development model. Data were collected through observation, interviews, questionnaires, and documentation. Functional testing was conducted using Black Box Testing, while feasibility assessment involved media experts, subject matter experts, and educators. All validation results were analyzed using a Likert Scale. The findings revealed that the educational game obtained a feasibility percentage of 90% from media experts and 92% from subject matter experts, both classified under the very feasible category, as well as 76% from educators, classified under the feasible category. Therefore, the educational game "Math Fraction Adventure" is considered feasible to be used as a learning medium to enhance students' understanding of fraction material.